A legal and comparative analysis of the independence of the Swaziland Competition Commission - Gule, Nomalanga Pearl (Department of Commercial Law, 2015)
Swaziland recently established a framework for enforcing competition law when it passed the Competition, Act 8 of 2007 (Swazi Competition Act). The Act provides for the establishment of the Swaziland Competition Commission (Swazi Commission), a statutory body responsible for the administration and enforcement of the Competition Act. One of its major objectives is to promote a secure and robust economic competition and consumer protection. Following its inception in 2007, the Swazi Commission has dealt with mergers and the question on the legality and enforcement of exclusionary clauses in contracts. These clauses are most prevalent in contracts for lease on property seeking to establish large shopping malls, as we shall see later from the case of Pick 'n Pay (Pty) Ltd v The Gables (Pty) Ltd. The adoption of a comprehensive competition law framework by Swaziland is relatively a new phenomenon and like other developing countries, the Swaziland competition regime presents some institutional challenges. Some of these challenges relate to the institutional structure of the Commission and its independence. Whether the independence of the Commission can be guaranteed in view of the manner it is constructed as well as the relationship between the Swazi Commission and the courts and finally, the jurisdictional powers of the Commission in the execution of its duties and functions in terms of the Act. These challenges taken together have a potential of undermining the independence and effectiveness of the only institution that has the mandate to create and ensure free and transparent markets in the country. This treatise seeks to analyse these challenges as presented by the Swaziland competition regime. A comparative analysis between Swaziland and the South African competition regime will be carried out in order to provide somewhat practical solutions to the challenges that Swaziland is confronted with. It is also aimed at setting out proposal for the reform of the competition framework of Swaziland to incorporate the bifurcated agency model as opposed to the integrated agency model it is currently structured on. Under the bifurcated agency model the Commission investigates all competition violations and then hand over the cases to a specialised tribunal for adjudication and enforcement. In the contrary the integrated agency model entails that the Commission investigates and make the first -level adjudication. The decision of the Commission can then be reviewed or appealed by the courts. This is the model adopted by Swaziland according to the Act.